Pelaksanaan Sistem Electronic Traffic Law Enforcement (E-TLE) Menggunakan Pengawasan CCTV Lalu Lintas Dalam Upaya Penertiban Pengguna Jalan di Kota Surabaya Pusat - Sakti, Harlu Aza Ayoma; H, Haniyah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
With the advancement of technology in various ways, the government has developed technology in traffic safety and road transportation by implementing the E-TLE system through CCTV traffic surveillance cameras, which are installed at certain points of the street. With the development of this security technology, it helps police in monitoring roads and traffic. The problem raised in this study is how the implementation of the E-TLE system through CCTV Traffic Surveillance in the effort to arrange road users in the City of Surabaya Center and discussed the problem of how the obstacles faced by the police in the application of the e-Tle system through monitoring of CCTV traffic in the efforts of arrange the user of the road in the city of Surabaya Centre. This type of research uses the type of empirical juridic research using the Qualitative Data Analysis Technique.The results of this research found barriers – barriers in its implementation namely, among other things, the capacity limitations and availability of E-TLE CCTV cameras from Korlantas, the disintegration of CCTV camera recording data E- TLE, and the partial understanding that e-tilang is not E-tLE. On the other hand, the problem of the two results of his research is the presence of obstacles – obstacles felt by the police in the application of E-TLE, among other things, the smooth monitoring of minimal officers and the prosecution of minor violations.